P 67 Satisfaction with and reliability of in-hospital video-electroencephalography monitoring systems in epilepsy diagnosis among German epilepsy centers. (May 2022) - Rosenow, F.; Baier, H.; Bien, C.G.; Bösebeck, F.; Dümpelmann, M.; Hamer, H.M.; Kellinghaus, C.; Knake, S.; Schreiber, M.; Surges, R.; Staack, A.M.; Tergau, F.; et al.
Abstract : Introduction: Video-electroencephalography monitoring (VEM) is the current gold standard for in-hospital epilepsy diagnosis as well as for the diagnostics of many other paroxysmal and recurrent neurological symptoms. Consequently, high-performance VEM systems (VEMS) have become indispensable for performing modern in-hospital differential and presurgical epilepsy diagnostics. As a central diagnostic tool and interface between technology and doctors, VEMS also represent a relevant safety factor in inpatient diagnostics. Recently, complaints about malfunctions of VEMS have been reported repeatedly, some of which hinder the clinical diagnosis of epilepsy patients. Therefore, we investigated the reliability of, customer satisfaction with and potential for improvement of the VEMS used in German epilepsy centres. Materials and Methods: Between December 2020 and January 2021, a survey was conducted among German epilepsy centres. Using a short questionnaire including established business to customer metrics, such as the Net Promoter Score, the Customer Satisfaction Score, the Customer Effort Score and the Things Gone Wrong Metric, the reliability, customer satisfaction and potential for general or specific improvements of VEMS were accessed without aiming to compare individual manufacturers or systems in detail. Results: A total of 16 of 27 contacted epilepsy centres (59%) participated in the survey. Customer satisfaction with VEMS was low with only 13 % of clients that would actively recommend their system to other clinicians or epileptologists. Only 50 % of users were satisfied with the overall performance of their VEMS, and only 18 % were satisfied with the manufacturer's after-sales service. Major software or hardware problems were reported in the diagnostic of approximately every 10th patient. Common problem areas mentioned were the VEMS user interface, the stability of software, a shortage of regular updates and a lack of customer-oriented improvements. The greatest potential for improvement was found in software and hardware stability as well as in customer service. Conclusion: As far as it can reasonably be assessed from this German multicenter survey, the level of satisfaction among German epilepsy centres regarding their VEMS is soberingly low. This unsatisfaction seems to be mainly based on frequent and sometimes serious malfunctions of hardware and software on the one hand and a subjective dissatisfaction with the manufacturer's aftermarket customer service on the other hand. The fact that on average the diagnosis of every 10th patient is hampered by hardware or software problems should be an alarming sign, regardless of the general satisfaction with VEMS. Besides the obvious potential for improvement, there is an urgent need for national and international functional and safety standards for VEMS.